Anisakis, Something Is Moving inside the Fish - María Teresa Audicana (Pathogens, 2022)
The first case of human infection by a species of the Anisakidae family was reported more than 60 years ago. Over the last 20 years, Anisakis has become a highly studied parasite, not only for its parasitism, but also for its role as an inducer of allergic reactions. Several studies have indicated that the pathological changes occurring within the gastrointestinal tract during infection with Anisakis simplex are the combined result of the direct action of the larvae invading the tissue and the complex interaction between the host’s immune system and the parasite. Although the most commonly described pathologies are digestive, urticaria/angioedema and anaphylaxis, occupational asthma and arthritis have been seldom described. This paper is a narrative of the immune-mediated reaction induced by this parasite over the course of the last two decades.